Sudden cardiac arrest secondary to cardiac amyloidosis in a young woman with cryopyrin-associated periodic syndrome. (16th April 2015) - Endo, Keiko; Suzuki, Atsushi; Sato, Kayoko; Shiga, Tsuyoshi
Abstract : Cryopyrin-associated periodic syndrome (CAPS) is caused by NLRP3 mutations, which result in dysregulated interleukin 1β (IL-1β) production and inflammation. Some patients with CAPS develop systemic amyloidosis via an inflammatory reaction. We describe a case of a 39-year-old woman who experienced cardiopulmonary arrest secondary to ventricular fibrillation complicated by cardiac amyloidosis as well as by CAPS. She was diagnosed with renal amyloidosis at 32 years of age. At 34 years of age, genetic sequencing of the NLRP3 gene demonstrated that she was heterozygous for the p.E304 K mutation, and she was subsequently diagnosed with CAPS. After treatment with canakinumab (human anti-IL-1β monoclonal antibody) for CAPS, the inflammatory reaction was improved. However, she eventually developed cardiac arrest with ventricular fibrillation and was successfully resuscitated. Echocardiography demonstrated mildly reduced left ventricular systolic function (left ventricular ejection fraction of 48%). Coronary angiography revealed no stenosis, but a cardiac biopsy demonstrated cardiac amyloidosis. She received an implantable cardioverter defibrillator.